Effects of neutral detergent fiber levels on apparent nutrient digestibility and intestinal microbiota composition and function in forest musk deer - Dai, Qindan; He, Yu; Wu, Jie; Zhou, Lei; Jiang, Guimei; Chen, Feng (Frontiers in Veterinary Science, 2025)
This experiment was conducted to explore the effects of different neutral detergent fiber (NDF) levels on nutrient apparent digestibility and intestinal microbiota composition and function in adult male forest musk deer (FMD) (Moschus berezovskii). A total of 18 adult male forest musk deer (FMD) (aged 4–10 years) with an initial average body weight of 7.09 ± 0.82 kg were selected and randomly divided into three groups with different NDF levels: L: 21.60%, M: 25.14%, and H: 28.47%. The FMD were used in a 50-day trial. The results showed that the apparent digestibility of NDF and acid detergent fiber (ADF) first increased and then decreased as NDF levels rose, with the M group showing the highest digestibility (p < 0.05). The H group exhibited significantly higher (p < 0.05) Chao1 and ACE indices compared to the L group. In addition, at the phylum level (the relative abundance > 0.5%), no significant differences were observed among the three groups, except for Mycoplasmatota, which showed higher (p < 0.05) relative abundance in the M group compared to the L group. At the genus level (the relative abundance > 1%), the three groups did not change (p > 0.05) significantly. In the KEGG function analysis, differentially expressed genes were primarily enriched in pathways related to organismal systems and human diseases. In the CAZy functional analysis, significant differences (p < 0.05) were observed in glycoside hydrolases (GHs) and carbohydrate-binding modules (CBMs), with the M group showing clear enrichment in fiber-degrading enzymes. Overall, the M group demonstrated superior NDF apparent digestibility and enhanced fiber degradation capacity. Therefore, a dietary NDF level of approximately 25% is recommended as optimal for adult male FMD.